Analysis of Abnormal Stock Returns Before and After The Rights Announcement - Ni Putu Yuria Mendra; Putu Wenny Saitri (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Right issue is a public offering that is only offered to old shareholders on a limited basis and provides a price lower than the market price which results in investors interested in buying it. An announcement that contains information will give an abnormal return to the market, otherwise if it does not contain it. Information then does not provide abnormal returns, abnormal returns can be used as a measuring instrument to see market reactions that occur. This study aims to identify whether there are differences in abnormal returns before and after the announcement of the rights issue. The analysis technique used in this research is an eleven-day event window consisting of five days before the announcement, one day of the announcement, and five days after the announcement. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. Determination of the sample using purposive sampling method and obtained as many as 50 samples of manufacturing companies. The data analysis technique used is the Wilcoxon Signed Rank Test.The results showed that there was no difference in abnormal returns before and after the announcement of the rights issue. The next researcher can add to the research period, pay more attention to the observation period (event window) used, and consider the company sector to be studied.